2016
DOI: 10.1111/apha.12760
|View full text |Cite
|
Sign up to set email alerts
|

Novel routes of albumin passage across the glomerular filtration barrier

Abstract: Albuminuria is a hallmark of kidney diseases of various aetiologies and an unambiguous symptom of the compromised integrity of the glomerular filtration barrier. Furthermore, there is increasing evidence that albuminuria per se aggravates the development and progression of chronic kidney disease. This review covers new aspects of the movement of large plasma proteins across the glomerular filtration barrier in health and disease. Specifically, this review focuses on the role of endocytosis and transcytosis of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
28
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 65 publications
(168 reference statements)
1
28
0
Order By: Relevance
“…A very recent report indicated that angiotensin‐II infusion induced albumin transcytosis through glomerular epithelial cells in the healthy rat kidney and analysis with a multi‐photon scope showed that 86% of the endocytosed albumin was moved via transcytosis to the urinary space (Schieß et al, ). Together, these reports strengthened the evidence for a transcellular pathway across glomerular epithelial cells (Castrop & Schieß, ). In vascular endothelial cells, albumin entered cells through caveolae (Li et al, ; Pascariu, Bendayan, & Ghitescu, ; Schubert et al, ) and was transported to the early endosomes, but did not reach the GA (Aoki, Hagiwara, Matsuzaki, Suzuki, & Takata, ) or lysosomes (Vogel, Minshall, Pilipović, Tiruppathi, & Malik, ).…”
Section: Discussionsupporting
confidence: 79%
“…A very recent report indicated that angiotensin‐II infusion induced albumin transcytosis through glomerular epithelial cells in the healthy rat kidney and analysis with a multi‐photon scope showed that 86% of the endocytosed albumin was moved via transcytosis to the urinary space (Schieß et al, ). Together, these reports strengthened the evidence for a transcellular pathway across glomerular epithelial cells (Castrop & Schieß, ). In vascular endothelial cells, albumin entered cells through caveolae (Li et al, ; Pascariu, Bendayan, & Ghitescu, ; Schubert et al, ) and was transported to the early endosomes, but did not reach the GA (Aoki, Hagiwara, Matsuzaki, Suzuki, & Takata, ) or lysosomes (Vogel, Minshall, Pilipović, Tiruppathi, & Malik, ).…”
Section: Discussionsupporting
confidence: 79%
“…Furthermore, insufficient transcytosis by dysfunctional PTCs also contributes to albuminuria. Under physiological conditions PTCs can reabsorb, transcytose Receptor-mediated albumin transcytosis in GECs has been proven to be involved in the formation of albuminuria [34] Podocytes Podocytes have the ability of albumin endocytosis and transcytosis [35,36,44,45,47,50,51,53] PTCs Defects of rat PTCs in endocytosis and transcytosis are involved in the pathogenesis of albuminuria [37,46,57] and process filtered albumin. Albumin is internalized to PTCs via megalin-cubilin-mediated, clathrin-dependent endocytosis.…”
Section: The Role Of Transcytosis In Albuminuriamentioning
confidence: 99%
“…Increasing evidence has shown that podocytes are able to endocytose and transcytose proteins [35,36,44,45]. Previous studies showed that cultured podocytes internalized albumin via transcytosis [36,[46][47][48].…”
Section: Transcytosis By Gecsmentioning
confidence: 99%
“…[62][63][64] Conversely, statins have been shown to reduce albumin endocytosis by PTCs and may enhance albuminuria. 65,66 Taking all the above into account, it could be postulated that the amount of albumin detected in a spot urine sample, which is the criterion in order to characterize a patient as having DN or not, is the net result of several parameters that are both patient related (degree of glomerular damage, proximal tubular integrity, serum albumin levels), but also health professionals related (use of therapeutic agents that influence glomerular filtration of albumin such as ACE-inh/ARBs or statins, or tubular processing of the filtered albumin like SGLT2 inhibitors, as well as the degree of hypertension, glycemic and lipids control in general).…”
mentioning
confidence: 99%